An Analysis of Students' Mathematical Adaptive Reasoning: The Impact of Creative Problem-Solving (CPS) Learning Model and Entrepreneurial Character - Komarudin Komarudin; Nadiyah Nur Sukardi; Yuberti Yuberti; Muhamad Afandi; Feli Ramury (Institut Agama Islam Negeri Curup, 2023)
This research aims to determine the effect of the CPS learning model on mathematical adaptive reasoning ability in terms of students' entrepreneurial character. This research is quantitative research of the quasi-experimental research design with a posttest-only control group design. The population was the eighth-grade students of SMP Negeri 1 Natar, consisting of 367 students. The sampling technique used was cluster random sampling. The data analysis technique employed was the two-way Anova test with a significance level of 0.05. The finding showed that there was an effect of the CPS learning model on students' mathematical adaptive reasoning ability. The CPS learning model provided higher results compared to the conventional learning model. Besides, the students' entrepreneurial character influenced their mathematical adaptive reasoning ability. Students with high entrepreneurial character had higher mathematical adaptive reasoning ability than those with low entrepreneurial character. However, the Tukey test result showed no interaction between the CPS learning model and entrepreneurial character on students' mathematical adaptive reasoning ability.